A first-in-man study to evaluate the safety, tolerability, and pharmacokinetics of pasireotide (SOM230), a multireceptor-targeted somatostatin analog, in healthy volunteers - Golor G; Hu K; Ruffin M; Buchelt A; Bouillaud E; Wang Y; Maldonado M (Dove Medical Press, 2012)
Georg Golor1, Ke Hu2, Matthieu Ruffin3, Alexandra Buchelt3, Emmanuel Bouillaud3, Yanfeng Wang2, Mario Maldonado31Parexel International GmbH, Berlin, Germany; 2Novartis Pharmaceuticals, East Hanover, NJ, USA; 3Novartis Pharma AG, Basel, SwitzerlandAbstract: Pasireotide (SOM230) is a multireceptor-targeted somatostatin analog with high binding affinity for four of the five somatostatin receptor subtypes (sst1,2,3 and sst5), and potential clinical activity in several neuroendocrine and oncologic conditions, including acromegaly, Cushing’s disease, and neuroendocrine tumors (NET). This manuscript reports the first-in-man dose-escalation study of pasireotide, evaluating its safety, tolerability, and pharmacokinetics (PK) in healthy male volunteers. A single dose of pasireotide 1–1200 µg was administered subcutaneously in four to eight subjects per dose level, with two additional subjects per cohort administered placebo. PK and safety evaluations were carried out over 7 days post-dose. Growth hormone (GH) suppression was evaluated using a GH-releasing hormone stimulation test on Day –1 and Day 1 at 3–5 hours post-injection. Seventy-two subjects completed the study. Pasireotide was well tolerated with no serious adverse events observed at any dose. Transient elevations in blood glucose levels were observed 2–6 hours after administration of pasireotide at doses between 200 µg and 1200 µg, but this resolved without intervention by 23 hours post-dosing. The maximum tolerable dose was not established within the tested range. Pasireotide demonstrated a favorable PK profile with fast absorption (tmax: 0.25–0.5 hours), low clearance (CL/F: 8–13 L/hour), long effective elimination half-life (mean t½,ß: 7–11 hours), and a proportional dose-exposure relationship. GH suppression of 79%–96% was observed at single pasireotide doses between 200 µg and 1200 µg. In conclusion, pasireotide demonstrated favorable safety, tolerability, and PK profiles, as well as promising activity in suppressing the release of GH. The efficacy and safety of pasireotide is currently being evaluated in patients with acromegaly, Cushing’s disease, NET, and various non-neuroendocrine disorders.Keywords: pasireotide, safety, tolerability, pharmacokinetics, healthy volunteers